Health and lifestyle issues among youth: A record analysis of contributing factors among beneficiaries attending youth mental health promotion clinics (Yuva Spandana Kendras) in Karnataka, India - Banandur S Pradeep; Mutharaju Arelingaiah; Sathya V Ramamurthy; Rache Suma; Nidhi Saraswat; Archana G Erappa Reddy; Hasiruvalli Gangappa Virupaksha; Lavanya Garady; Vani Naik; Subhash Chandra Lakshminarayan; Shalini Rajaneesh; Gopalkrishna Gururaj; et al. (Wolters Kluwer Medknow Publications, 2023)
Background: Youth are considered to be most vulnerable to health and lifestyle issues (HLS) in India. The current study aims to investigate the factors that contribute to health and lifestyle issues among youth attending mental health promotion clinics (YMHP) in Karnataka. Method: Three-year first-visit data from beneficiaries (aged 15-35 years) attending YMHP clinics in Karnataka between 2017 and 2020 were analyzed. Multivariable logistic regression analysis included beneficiaries reporting any HLS issue as the outcome and a host of 57 hypothesized variables as exposures. Results: Overall, 2,615 (25%) beneficiaries reported HLS issues. Years of schooling (AOR 5-7 years = 0.89; 95% confidence interval [CI] =0.60-1.31), (AOR 8-10 years = 0.65; 95% CI = 0.46-0.91), (AOR >10 years = 0.67; 95% CI = 0.49-0.93)], unemployed youth (AOR = 0.52; 95% CI = 0.45-0.61) business and salaried workers (AOR = 1.69; 95% CI = 1.33-2.13), and other occupations (AOR = 2.11; 95% CI = 1.73-2.56), junk food consumption (AOR = 0.76;95% CI = 0.68-0.84), having issues related to relationships with parents (AOR = 3.01; 95% CI = 2.47-3.68) and intergenerational issues (AOR = 1.71; 95% CI = 1.19-2.45), self-development issues (AOR low-self-awareness = 1.57; 95% CI = 1.33-1.85), (AOR low-self-esteem = 1.29; 95% CI = 1.062-1.57), (AOR emotional issues = 1.57; 95% CI = 1.31-1.89), education and academics (AOR = 1.23; 95% CI = 1.09-1.39), safety issues (AOR = 4.11; 95% CI = 3.07-5.50), gender sex and sexuality issues (AOR = 2.44; 95% CI = 1.43-4.15), suicidal ideation (AOR = 1.91; 95% CI = 1.44-2.54), substance use (AOR tobacco chewing = 1.45; 95% CI = 1.09-1.93), (AOR tobacco-smoking = 1.66; 95% CI = 1.18-2.32), (AOR smoking = 4.94; 95% CI = 3.52-6.93) and experiencing emotions (AOR feel anxious = 1.63; 95% CI = 1.41-1.88), (AOR forgetfulness = 1.50; 95% CI = 1.41-1.98), (AOR difficulty in concentration = 1.37; 95% CI = 1.035-1.81), (AOR anger = 1.61; 95% CI = 1.25-2.07), (AOR feel worthless = 2.21; 95% CI = 1.71-2.86) were associated with HLS issues among beneficiaries. Conclusion: This analysis addresses an important but neglected component of HLS issues among youth highlighting the importance of early intervention among youth to prevent the development of diseases later in life. The study has important implications for youth health promotion in India and countries such as India. Health and Lifestyle Issues Among Youth: A record analysis of contributing factors among beneficiaries attending Youth Mental Health promotion clinics (Yuva Spandana Kendras) in Karnataka, India.